Expectations of doctoral students in the field of medicine and health sciences towards a graduate school: an online cross-sectional survey in Germany - Stock-Schröer, Beate; Lange, Silke (Frontiers in Medicine, 2024)
The doctoral thesis in medicine is a special case, as it is usually started during the course of study and the students have no experience of scientific work. This lack of scientific training is often criticized, and the quality of doctoral theses in medicine is considered low. In order to increase the quality of doctoral theses and the successful completion rate, a structured doctoral programme can provide the appropriate support. A cross-sectional survey of doctoral students in the field of medicine and health sciences was conducted to assess their expectations of a structured programme offered by a graduate school planned for doctoral studies in complementary and integrative medicine (CIM). Among other questions concerning experiences in their doctorate, the participants were asked to indicate their expectations in two free text answers and 24 pre-defined answers (5-point Likert scale). In addition, participants were asked how supervision should be organized in the curriculum. The majority of the participants expected individual personal support and advice in the graduate school, while financial support was not very important for them. In addition to the scientific training, networking and support among the participants of the graduate school was considered important. The non-medical participants were interested in personality development in science and networking with other doctoral students, whereas the medical doctoral students were more interested in scientific guidance. Doctoral students with a CIM topic expected a predicate and a better final grade by participating in such a graduate school. These results provide important information on how the curriculum in the graduate school should be designed. The next steps will be to evaluate the preliminary curriculum in order to develop a curriculum following the six-step approach of Kern.